The anti-cancer activity of extracts derived from millets and Kraalbos - Mohamed, Luqmaan (Department of Human Biology, 2022)
Breast cancer is the second most commonly diagnosed cancer and the leading cause of cancer deaths in women. Several factors, such as the costs of anti-cancer drugs, drug resistance and relapse, make it difficult to treat this disease effectively. In the South African context this is exacerbated by poor socio-economic conditions. Thus, there is a dire need to develop novel anti-breast cancer drugs which are safe, effective and cheap. In this regard, natural products serve as a highly exploitable medicinal resource and indeed, many successful commercially available drugs have been derived from natural products. Plants, especially those used as food or medicine, are a particularly robust source of beneficial phytochemicals. Thus, this study investigated the anti-cancer effects of extracts derived from three varieties of African millets as well as from the indigenous Kraalbos plant, Galenia africana, against the MCF-7 oestrogen receptor positive and the MDA-MB-231 triple negative breast cancer cell lines. The millet extracts tested were derived from Sorghum bicolor (Enforcer), Pennisetum glaucum (Babala) and Eragrostis tef (Tef) using both a reflux-based and a cold extraction procedure. MTT assays reveal that the millet extracts derived from the reflux-based extraction show no short-term cytotoxicity against both breast cancer cell lines tested. Extracts derived from the cold extraction were subjected to fractionation using HPTLC. Results from these extracts show that only the methanol fractions of the Babala and Enforcer millets exhibited short-term cytotoxic activity against the MCF-7 and the MDAMB- 231 breast cancer cell lines. Five Kraalbos extracts (KB1, KB2, KB3, KB4 and KB5) were tested for their short-term cytotoxicity against the MCF-7 and MDA-MB-231 breast cancer cell lines. KB2 was found to display the most potent activity and its anti-cancer activity was characterized further. Clonogenic assays revealed that KB2 also displayed long-term cytotoxicity against breast cancer cells but not normal breast epithelial cells. Scratch motility assays and western blotting with antibodies to epithelial to mesenchymal transition markers showed that KB2 inhibited the migratory ability of breast cancer cells. To understand the mechanism(s) underpinning the anti-cancer activity of KB2, ROS-GloTM H2O2 and GSH-GloTM Glutathione assays were performed and the results revealed that KB2 induced the production of reactive oxygen species. Furthermore, western blotting with antibodies to γH2AX showed that KB2 induced double strand DNA breaks in breast cancer cells. Flow cytometry and western blotting with antibodies to p53, p21, cyclin A and cyclin B1 further revealed that KB2 causes breast cancer cells to arrest in the S and G2/M phases. A sub-G1 peak, indicative of cell death, was also observed in the flow cytometry analyses. Indeed, using western blotting with antibodies to markers of apoptosis (caspases 3, 7, 8, and 9 and PARP) and necroptosis (p-MLKL and p-RIP3) KB2 was found to induce cell death via the intrinsic and extrinsic apoptotic pathways and necroptosis. Western blotting and immunocytochemistry with an antibody to LC-3 also showed that KB2 induces autophagy in the breast cancer cells but whether it functions as a pro-death or pro-survival mechanism remains to be elucidated. Taken together, this study demonstrates that extracts derived from millets and Kraalbos show anti-cancer activity against oestrogen receptor positive and triple negative breast cancer cells and that KB2 is worth progressing to pre-clinical studies.